Skip to content
New issue

Have a question about this project? Sign up for a free GitHub account to open an issue and contact its maintainers and the community.

By clicking “Sign up for GitHub”, you agree to our terms of service and privacy statement. We’ll occasionally send you account related emails.

Already on GitHub? Sign in to your account

Explain the rule of resolution using boolean logic #8

Open
wants to merge 1 commit into
base: main
Choose a base branch
from
Open
Changes from all commits
Commits
File filter

Filter by extension

Filter by extension

Conversations
Failed to load comments.
Loading
Jump to
Jump to file
Failed to load files.
Loading
Diff view
Diff view
28 changes: 16 additions & 12 deletions src/internals/incompatibilities.md
Original file line number Diff line number Diff line change
Expand Up @@ -89,28 +89,32 @@ With incompatibilities, we would note
\Rightarrow \quad \\{ a: T_a, c: \overline{T_c} \\}. \\]

This is the simplified version of the rule of resolution.
For the generalization, let's reuse the "more mathematical" notation of conjunctions
for incompatibilities \\( T_a \land T_b \\) and the above rule would be
For the generalization, let's write them as [boolean expressions][boolean_expression].

\\[ T_a \land \overline{T_b}, \quad
T_b \land \overline{T_c} \quad
\Rightarrow \quad T_a \land \overline{T_c}. \\]
\\[ \neg (T_a \land \overline{T_b}) \quad \land \quad
\neg (T_b \land \overline{T_c}) \quad
\Rightarrow \quad \neg (T_a \land \overline{T_c}). \\]

In fact, the above rule can also be expressed as follows

\\[ T_a \land \overline{T_b}, \quad
T_b \land \overline{T_c} \quad
\Rightarrow \quad T_a \land (\overline{T_b} \lor T_b) \land \overline{T_c} \\]
\\[ \neg (T_a \land \overline{T_b}) \quad \land \quad
\neg (T_b \land \overline{T_c}) \quad
\Rightarrow \quad \neg (T_a \land (\overline{T_b} \lor T_b) \land \overline{T_c}) \\]

since for any term \\( T \\), the disjunction \\( T \lor \overline{T} \\) is always true.
In general, for any two incompatibilities \\( T_a^1 \land T_b^1 \land \cdots \land T_z^1 \\)
and \\( T_a^2 \land T_b^2 \land \cdots \land T_z^2 \\) we can deduce a third,
called the resolvent whose expression is
In general, for any two incompatibilities \\( \\{ a: T_a^1, \cdots, z: T_z^1 \\} \\) and
\\( \\{ a: T_a^2, \cdots, z: T_z^2 \\}, \\)
or

\\[ (T_a^1 \lor T_a^2) \land (T_b^1 \land T_b^2) \land \cdots \land (T_z^1 \land T_z^2). \\]
\\[ \neg (T_a^1 \land T_b^1 \land \cdots \land T_z^1) \land \neg (T_a^2 \land T_b^2 \land \cdots \land T_z^2), \\]
we can deduce a third, called the resolvent whose expression is

\\[ \neg ((T_a^1 \lor T_a^2) \land (T_b^1 \land T_b^2) \land \cdots \land (T_z^1 \land T_z^2)). \\]

In that expression, only one pair of package terms is regrouped as a union (a disjunction),
the others are all intersected (conjunction).
If a term for a package does not exist in one incompatibility,
it can safely be replaced by the term \\( \neg [\varnothing] \\) in the expression above
as we have already explained before.

[boolean_expression]: https://en.wikipedia.org/wiki/Boolean_expression#Boolean_operators